The modern approach to number work to the deaf (preparatory level) - Fernandez, Milagros B. 1944- (College of Education, University of the Philippines Diliman, 1969)
This paper is focused on the solution to the problem of how to make a deaf child understand and learn more mathematics and develop a deeper appreciation of it and how to provide a rich background of numerical experiences for the deaf in the classroom. The writer made use of the different books, workbooks, guides and periodicals in exploring and expounding the teaching of Modern Mathematics to the deaf child in the preparatory level.